2007
DOI: 10.1158/0008-5472.can-06-3996
|View full text |Cite|
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Sensitize Prostate Cancer Cells to Agents that Produce DNA Double-Strand Breaks by Targeting Ku70 Acetylation

Abstract: This study reports a histone deacetylation-independent mechanism whereby histone deacetylase (HDAC) inhibitors sensitize prostate cancer cells to DNA-damaging agents by targeting Ku70 acetylation. Ku70 represents a crucial component of the nonhomologous end joining repair machinery for DNA double-strand breaks (DSB). Our data indicate that pretreatment of prostate cancer cells with HDAC inhibitors (trichostatin A, suberoylanilide hydroxamic acid, MS-275, and OSU-HDAC42) led to increased Ku70 acetylation accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
145
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 36 publications
11
145
0
Order By: Relevance
“…DNA damage has been described previously, and recent findings raise the possibility that ROS generation or perturbations in the DNA repair machinery may be involved in this process (5,8,26,41). To characterize the relationship between these events in greater detail, evidence of oxidative DNA damage was monitored by confocal microscopic analysis of XRCC1, a component of the base excision repair system and early response protein recruited at the site of single strand breaks (SSBs), (42) (DSBs).…”
Section: Lbh-589-induced Nf-b Activation Protects Cells From Rosmediamentioning
confidence: 99%
“…DNA damage has been described previously, and recent findings raise the possibility that ROS generation or perturbations in the DNA repair machinery may be involved in this process (5,8,26,41). To characterize the relationship between these events in greater detail, evidence of oxidative DNA damage was monitored by confocal microscopic analysis of XRCC1, a component of the base excision repair system and early response protein recruited at the site of single strand breaks (SSBs), (42) (DSBs).…”
Section: Lbh-589-induced Nf-b Activation Protects Cells From Rosmediamentioning
confidence: 99%
“…This suggests that tubacininduced accumulation of DNA breaks in LNCaP cells cultured with SAHA may result in part from an impaired capacity for DNA DSB repair. Several proteins involved in the DNA damage repair pathway are targets of lysine acetylation (40), and acetylation of DNA repair proteins has been shown to alter their activity (41,42). HDAC6 has a role in the removal of misfolded and damaged proteins through its ability to recruit polyubiquitinated proteins to dynein motors and transporting them to aggresomes (15,43).…”
Section: Discussionmentioning
confidence: 99%
“…Treatments with the HDACIs TSA, SAHA, MS-275 and OSU-HDAC42 leads to acetylation of Ku70, a key NHEJ component, and sensitizes prostate cancer cells to DNA-damaging agents. This study showed that Ku70 acetylation does not affect the formation of a complex with its natural partner, Ku80; but, when the authors mimicked acetylation by replacing key lysines with glutamines, the ability of Ku70 to bind DNA extremities was suppressed [65]. involved in both DSB sensing and repair) [66].…”
Section: Hdaci and Double Strand Break Repair Machinerymentioning
confidence: 94%